World viewed challanges of bioethics - Dębowski, Jan (Studia Ecologiae et Bioethicae, 2007)
The article includes detailed analysis of basic relations between bioethics and other sciences, the author shows relation between bioethics and theology, he presents basic moral dilemmas of bioethical researches and elementary justification of the need of responsibility ethics.